Self-Healing in Traditional Chinese Medicine - Navarro, Francisco A (Archīum Ateneo, 2020)
In this lecture, Dr. Navarro talks about the foundational concepts of Traditional Chinese Medicine, and Eastern perspectives on science and the human body. Sharing his experience as a medical doctor, he recommends ways to help us understand and maintain our health. Speaker: Francisco A Navarro is a doctor and practitioner of Traditional Chinese Medicine (TCM). His medical practice integrates modern conventional therapies with traditional therapies of acupuncture, moxabustion, tuina, cupping, and qigong. Dr. Navarro has been a teacher at Ateneo De Manila University Chinese Studies Program for 15 years, and heads a post-graduate training program in TCM and acupuncture for medical doctors.